P43 Do changes in objective outcome measures match patient-reported experience of pulmonary rehabilitation?. (16th November 2010) - Fowler, RP; Ingram, KA; Clark, AL; Nolan, CM; Man, WD
Abstract : Introduction: There are a variety of different objective outcome measures that are currently used to assess patients′ response to pulmonary rehabilitation (PR) and the effectiveness of service delivery. Most of these measures have well defined minimal clinically important difference (MCID) thresholds, including the Incremental Shuttle Walk (ISW), Chronic Respiratory Questionnaire (CRQ) and the Hospital Anxiety and Depression scale (HAD). However, it is not clear how many outcome measures are needed to encapsulate patient-reported improvement following PR. Methods: 101 patients, completing an 8 week supervised outpatient pulmonary rehabilitation programme, were asked to rate their response with the following question: 'How do you feel your overall condition has changed after rehabilitation?' Responses were categorised according to a Likert scale ranging from 1 'I feel much better' to 5 'I feel much worse'. All patients were blinded to the results of their objective assessments. For every patient responding category 1, we determined whether the MCID was achieved for each of seven different outcome measures: the ISW (>48 m), the four domains of the CRQ (mean change >0.5 per domain), HAD-anxiety (<−1.5) and HAD-depression (<−1.5). Results: 64 patients (63%) recorded a response of 'I feel much better'. Of these, the proportion of patients achieving the MCID for the seven different outcome measures is seen in Abstract P43 Table 1 below. 6 patients (9%) achieved the MCID for all outcome measures tested, whilst one patient (1.6%) did not achieve the MCID in any of the outcome measures. Four patients (6.25%) did not achieve the MCID in either the ISW or any of the CRQ domains. Discussion: Patient-reported positive response to PR is probably determined by several factors, which differ from individual to individual, and cannot be captured by use of only one outcome measure. More than 98% of patients who reported feeling much better following pulmonary rehabilitation achieve the MCID in at least one of ISW, CRQ domains or HAD.